Theorizing the virus: abjection and the COVID-19 pandemic. Issue 9 (16th September 2020) - Pfaller, Larissa
Abstract : Purpose: Using Kristeva's theory of abjection, this article analyzes the psychosocial reality of the coronavirus disease 2019 (COVID-19) pandemic, advancing the understanding of exclusion and stigmatization as forms of social abjection. Design/methodology/approach: The article applies abjection to understand how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is both a medical emergency but also a cultural challenge. The analysis is structured in three dimensions: (1) the transgressive potential of the virus, (2) forms of cultural coping with its threat and (3) the moral order of abjection. Findings: The virus is an existential challenge to cultural boundaries and subjectivity. Strategies to prevent its further spread (e.g. handwashing, "social distancing" and closing national borders) are thus culturally significant. The virus triggers the processes of abjection, (re-)establishing challenged boundaries and exclusionary social hierarchies. Collateral consequences of protective measures vary across regions and social groups, creating and exacerbating social inequalities. Research limitations/implications: Practices of abjecting the virus go far beyond handwashing, masking, etc. The virus, an invisible enemy to be expunged, is also a hybrid of threatening pathogen and human body; it is not the virus but people who experience exclusion, discrimination and disrespect. Thus, cultural sociology must address the moral economy of abjection. Social implications: As Kristeva insists, the abject threatens both the subject and the symbolic order. Overcoming social abjection means recognizing and strengthening individual and community agency and requires understanding vulnerability as an anthropological condition, enacting caring relationships and acting in solidarity. Originality/value: This article demonstrates that abjection is a suitable theoretical tool for analyzing the social dynamics of the COVID-19 crisis.